La canzone di Jordan Bonel S’ira d’amor tenges amic iauzen (BdT 273,1) e alcuni problemi nell’edizione critica dei testi trobadorici - Stefano Resconi (Perspectives Médiévales)
Some of the most peculiar features of the manuscript troubadouresque tradition – few examples of genuine errors and textual contamination – make it particularly difficult to apply strictly on Lachmann's methodological principles when such texts are considered under a critical scrutiny. This article exposes a body of procedures that can be used in order to address and trace back the genealogical links between various texts, one that can be applied even in the most complex cases. More specifically, such procedures rely on a cautious assessment of the different types of textual innovations, in view of their integration in a broader, coherent system. An example of such procedures will be given through the study of the manuscript tradition of one of the rare troubadouresque texts not to have been published in a scientific edition yet: Jordan Bonel's S’ira d’amor tenges amic iauzen  (BdT 273,1), of which the first ever critical edition will be provided here.